The Influence of Health Promotion Through Social Media Whatsapp on the Knowledge of Adolescent Girls About Personal Hygiene with Vaginitis Symptoms - Siregar, Hajari Rodiah (International Journal of Medicine And publich Health, 2025)
Young women are susceptible to vaginitis if they do not maintain vaginal hygiene. Vaginitis occurs in women who have entered puberty or will enter menopause with risk factors such as lack of hygiene, unprotected sexual intercourse, with multiple partners, sexually transmitted diseases and others. Personal hygiene needs to be considered because it is related to the incidence of genital infections. The most common vaginitis is bacterial vaginosis, trichomoniasis and vulvovaginal candidiasis. This study aims to determine whether there is an effect of health promotion through social media whatsapp on the knowledge of ninth grade female adolescents about personal hygiene with symptoms of vaginitis at SMP Negeri 02 Class IX Panyabungan Mandailing Natal Regency in 2025. The type of research used is Pre-Experimental research. The population in the study were all ninth grade female adolescents at SMP Negeri 02 Class IX Panyabungan Mandailing Natal Regency in 2025. The sampling technique used purposive sampling with a sample size of 41 people. using the Wilcoxon test. The results of the study obtained an average knowledge before (7,561) and after (12,048). The results of the Wilcoxon test obtained a p value = 0.000 <0.05 which indicates that there is an effect after being given health promotion through WhatsApp social media about personal hygiene in adolescents at SMP Negeri 02 Class IX Panyabungan Mandailing Natal Regency in 2025. WhatsApp social media can be used as a reference for modern learning in conveying information to provide health promotion about personal hygiene with symptoms of vaginitis in adolescents to increase knowledge so that adolescents are prevented from vaginal diseases.